Electrocardiographic effects of class 1 selective histone deacetylase inhibitor romidepsin. (27th April 2015) - Sager, Philip T.; Balser, Barbara; Wolfson, Julie; Nichols, Jean; Pilot, Richard; Jones, Suzanne; Burris, Howard A.
<x xml:space="preserve">Abstract</x> The available data support the absence of a major effect of romidepsin on the QTc interval. Administration of certain antiemetics and patient hypomagnesemia/hypokalemia can impact the QT interval, thus electrolyte levels should be kept in the normal range and consideration should be exercised when administering romidepsin with antiemetics and other drugs that prolong the QTc interval. <boxed-text content-type="graphic" id="cam4467-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>